(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aims to measure the effectiveness of digital government communication on Platform X in reaching local audiences through an applied study of the official account of the Eastern Province Municipality. The study is grounded in the rapid transformations of government communication, as social media platforms have become essential tools for disseminating information, enhancing transparency, and enabling direct interaction between government institutions and the public. In the context of Saudi Arabia’s digital transformation under Saudi Vision 2030, the study highlights the importance of examining the extent to which local government accounts can achieve meaningful audience reach rather than merely publishing communication messages. The study adopts a descriptive-analytical approach and a media survey method, using a questionnaire to collect data from a sample of 400 members of the local audience who follow the official account of the Eastern Province Municipality on Platform X. It focuses on analyzing the nature of the published communication content, measuring audience engagement through digital indicators such as likes, reposts, and comments, and examining the communication factors that affect effectiveness, including message clarity, content diversity, posting regularity, and the relevance of content to local audience interests. The study is theoretically grounded in Media Richness Theory and Media Dependency Theory. Media Richness Theory helps explain how diverse and interactive content forms may enhance understanding and reduce ambiguity, while Media Dependency Theory explains the extent to which audiences rely on the official account as a source of information related to municipal services and activities. The significance of this study lies in providing both scholarly and practical insights into the effectiveness of local digital government communication, contributing to the development of institutional communication strategies, improving public engagement, and strengthening the reach of government messages to beneficiaries in the Eastern Province.